Levels of Depression, Anxiety and Stress in Boxing Athletes Facing Pre-POPNAS Selection - Haryani, Meri; Nurkhoiroh, Nurkhoiroh; Irawan, Safri; Prasetyo, Agung; Mile, Rifky (Universitas Negeri Padang, 2024)
Stress and anxiety are often experienced by boxing athletes, especially when facing national or international competitions such as the National Student Sports Week Prequalification Selection Championship (PRA-POPNAS). Internal and external pressure, including coaches' demands to achieve victory targets, as well as intensive training programs, often affect athletes' mental conditions. This research aims to determine differences in levels of stress, anxiety and depression in boxing athletes. Using descriptive quantitative methods, the research involved 32 boxing athletes as samples using total sampling techniques. Data was collected using the Depression, Anxiety, Stress Scale (DASS-42) which has been adapted to Indonesian. Data analysis includes descriptive analysis, homogeneity test, normality test, and t test. The research results showed that 88% of athletes experienced stress, with the highest category being severe stress. As many as 91% of athletes experienced anxiety, especially very severe anxiety, while depression was detected in 53% of athletes, with the highest category being mild depression. These findings highlight the importance of paying attention to the mental health of boxing athletes when facing the stress of competition.